PENERAPAN ACCRUAL BASIS PADA PELAPORAN KEUANGAN UMKM BERDASARKAN SAK ETAP DI KOPERASI KARYAWAN PT. BANK SULUT - Motto, Agita; Ilat, Ventje; Kalalo, Meyli (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
MSME is regulated based on Law No. 20 Year 2008 on Micro Small Medium Enterprises. In practice in the field of many MSMEs pelaprannya not adequate because sebagia still use the cash basis in penyilasianya and presentation of financial statements. Financial reporting of MSMEs should be prepared based on SAK ETAP and using accrual basis. The purpose of this research is to apply financial report of Cooperative UMKM based on SAK ETAP. The research method used is descriptive qualitative, where the qualitative data is the information data in the form of verbal sentence is not a symbol of numbers or numbers. Qualitative data obtained through a process using in-depth analysis techniques and can not be obtained directly. The results showed that the Employee Cooperation of PT.Bank Sulut which broperasi field of Java that is saving and loan services as well as vehicle rental, cloth factory. Transactions are recorded on an accrual basis system where transactions are recognized when they occur rather than when cash is received.Keywords: MSME, Financial Statement, SAK ETAP